2015
DOI: 10.1093/cid/civ974
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Infectious Mastitis by Oral Administration ofLactobacillus salivariusPS2 During Late Pregnancy

Abstract: NCT01505361.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 37 publications
3
113
0
3
Order By: Relevance
“…Other authors have suggested that metabolites with antibacterial properties produced by probiotic strains might reach the mammary gland and affect survival or virulence of Staphylococcus . 11 L. fermentum showed in vitro the capability of inhibiting Staphylococcus growth in a diffusion agar assay, evidencing the production of antibacterial compounds that were not identified. 16 In contrast, L. fermentum CECT5716 has shown immunoenhancing activity by increasing immunoglobulins and Th1 cytokines such as tumor necrosis factor (TNF)-α and IL-12.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other authors have suggested that metabolites with antibacterial properties produced by probiotic strains might reach the mammary gland and affect survival or virulence of Staphylococcus . 11 L. fermentum showed in vitro the capability of inhibiting Staphylococcus growth in a diffusion agar assay, evidencing the production of antibacterial compounds that were not identified. 16 In contrast, L. fermentum CECT5716 has shown immunoenhancing activity by increasing immunoglobulins and Th1 cytokines such as tumor necrosis factor (TNF)-α and IL-12.…”
Section: Discussionmentioning
confidence: 96%
“…Mastitis incidence reported by studies using the same diagnosis criteria of L. fermentum consumption was slightly lower, between 13% and 20%. 10,11,20 It has been previously reported that antibiotherapy during delivery was significantly more widely administered to women reporting mastitis (OR 1.53). 22 These data might explain the slightly higher incidence observed in the L. fermentum study because women who received preventive antibiotic in the context of delivery were recruited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, findings from a recent randomised trial revealed that two strains of lactobacilli, Lactobacillus salivarius and Lactobacillus fermentum provided some evidence as to their effectiveness as alternatives to antibiotics for the treatment of mastitis [36]. One of these strains, Lactobacillus salivarius, has recently been investigated for the prevention of mastitis [37]. This study, along with previous animal studies have shown promising results [38].…”
Section: Introductionmentioning
confidence: 94%
“…Совсем недавно также был исследован потенциал L. salivarius PS2 по предотвращению мастита при перораль-ном введении на последних сроках беременности для женщин, которые страдали от инфекционного мастита после, по крайней мере, предыдущей беременности [26]. В общей сложности было исследовано 108 беременных женщин, разделенных на две группы.…”
Section: мастит: мишень для пробиотиков?unclassified